Emerging Trends in the Social and Behavioral Sciences 2015
DOI: 10.1002/9781118900772.etrds0106
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Trends in Social Network Analysis of Terrorism and Counterterrorism

Abstract: A key issue in tracking transnational terror trends is the utility of social network analysis, both as a theoretical perspective and as a methodological toolkit, for understanding and assessing terror organizations, and for developing counterterror policies and practices to detect and disrupt terror attacks. Foundational efforts were case studies of particular groups or operations, culling data from newspaper reports and court trial documents, then creating matrix files for analysis with social network compute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Another important issue related to the structural analysis of social networks is to investigate the presence of spams, malicious activities, anomalies, and frauds within a network. 46 These events can be in any form such as cyber bullying, 47,48 terrorist attack planning, 49 embezzlement, 50 dissemination of fraud news, 51 fake accounts to create artificial numbers on pages, 52,53 and political manipulation. 54,55 Beutel et al suggested a system in which a bipartite graph is created between users and pages they liked.…”
Section: Applications Of Structural Analysismentioning
confidence: 99%
“…Another important issue related to the structural analysis of social networks is to investigate the presence of spams, malicious activities, anomalies, and frauds within a network. 46 These events can be in any form such as cyber bullying, 47,48 terrorist attack planning, 49 embezzlement, 50 dissemination of fraud news, 51 fake accounts to create artificial numbers on pages, 52,53 and political manipulation. 54,55 Beutel et al suggested a system in which a bipartite graph is created between users and pages they liked.…”
Section: Applications Of Structural Analysismentioning
confidence: 99%
“…actions, forcing them to find compromise between security and communication [211,212]. Typically, leadership roles are re-adjusted and hierarchical organizations become more decentralized so that the network may survive a negative environment.…”
Section: Lattice and Network Modelsmentioning
confidence: 99%
“…These visual maps resemble complex webs or multiple conjoined hub–spoke models depending on the complexity of the analysis (see, e.g., Easley and Kleinberg, 2010). SNA has thus become a conventional metaphor guiding research into social collectivities — normally organisations — as diverse as cities, governments and terrorists (Giuffre, 2013; Knoke, 2015; Rhodes, 1990). Insofar as it has become a methodological tool, it elides its metaphorical nature — particularly its representation of the world through the hub–spoke model first seen in concepts of the communicative interconnections forged by the telegraph — presenting itself as a simple description of social, economic and political reality.…”
Section: Network Thinking: a Brief Historymentioning
confidence: 99%